Reliability of neurometabolite detection with two‐dimensional localized correlation spectroscopy at 3T. Issue 6 (23rd April 2018) - Arm, Jameen; Al‐iedani, Oun; Quadrelli, Scott; Ribbons, Karen; Lea, Rod; Lechner‐Scott, Jeannette; Ramadan, Saadallah
Abstract : BACKGROUND: Two‐dimensional localized correlational spectroscopy (2D L‐COSY) has been applied in vivo to investigate metabolic profiles in many disorders due to its ability to detect several metabolites simultaneously. Successful application of this technique depends on the reliability of the detection and understanding of the variability result from test–retest measurements. PURPOSE: To evaluate the test–retest repeatability/reliability of 2D L‐COSY in detecting brain metabolites in a phantom and healthy subjects in a 3T scanner. STUDY TYPE: Test–retest.POPULATION/PHANTOM: Six healthy subjects and magnetic resonance spectroscopy–high definition (MRS‐HD) sphere or "Braino". FIELD STRENGTH/SEQUENCE: 3T/2D L‐COSY MRS. ASSESSMENT: Healthy subjects underwent eight weekly experiments over a period of 3 months with an intersession delay of 1 month after the first four measurements. Twenty‐nine neurometabolite resonances (8 diagonal, 14 cross, and 7 composite resonances) were studied using a 27 cm 3 voxel from the posterior cingulate cortex. In vitro evaluations were performed in a similar manner as in vivo on a Braino phantom containing brain metabolites at physiological concentrations and pH. STATISTICAL TESTS: Intra‐ and intersubject variability were measured. Test–retest repeatability was calculated using coefficient of variation (CV), and reliability was assessed with standard error measurement (SEM) and intraclass correlation coefficient (ICC), using SPSS software. RESULTS: The intra/inter CV for in vitro and in vivo data ranged from 0.01–0.23%/0.02–0.29% and 0.03–0.23%/0.04–0.39%, respectively. The major diagonal peaks showed ICC ranging from 0.31 to 0.93, while the ICC for cross peaks were 0.09–0.87. The SEM for in vivo data ranged from 0.0016 to 0.08. The interweek interval may have a positive effect on metabolite ratios ( P = 0.08; F = 1.78). DATA CONCLUSION: The low variability in metabolite concentration in this study shows a high level of reliability of 2D L‐COSY in the human brain. Level of Evidence: 2 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2018;48:1559–1569